Exploration of Mothers’ Perceptions and Barriers in Stunting Prevention: A Phenomenological Study of Families with Stunted Toddlers - Ruminta Sirait; Nilawati; Marta Imelda Br Sianturi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Stunting remains a significant public health challenge in Indonesia, particularly in Aceh Province, which recorded a prevalence of 28.6% in 2024. This study employs a descriptive phenomenological approach to explore maternal perceptions and barriers toward stunting prevention in Gele Lah Village, Central Aceh Regency. Data were collected through in-depth interviews, participant observation, and secondary document reviews involving eight primary informants and two key informants between January and February 2025, with analysis conducted using the Colaizzi method. The findings identified eight stunted toddlers and revealed primary barriers including the normalization of the condition through genetic attribution, social stigma associated with the stunting label, the practice of feeding